2021
DOI: 10.1101/2021.05.28.446057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simple and effective serum-free medium for sustained expansion of bovine satellite cells for cell cultured meat

Abstract: Cell-cultured meat offers the potential for a more sustainable, ethical, resilient, and healthy food system. However, research and development has been hindered by the lack of suitable serum-free media that enable the robust expansion of relevant cells (e.g., muscle satellite cells) over multiple passages. Recently, a low-cost serum-free media (B8) was described for induced pluripotent stem cells. Here, we adapt this media for bovine satellite cells and show that the addition of a single component, recombinant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 34 publications
(47 reference statements)
0
23
0
Order By: Relevance
“…Although the initial cell adhesion efficiency and cell viability were low during cell culture using a serum-free medium, the cell growth efficiency was improved to a value close to that of the serum-containing medium through partial medium replacement and removal of antibiotics. In another study, Stout et al (2021) found that cell activity was maintained by subculturing bovine satellite cells in a serum-free medium and evaluated the possibility of reducing the medium cost by predicting the optimal amount of medium and additives. In particular, long-term cell expansion was possible when recombinant albumin was added to the developed Beefy-9 medium.…”
Section: Current Technologies In the Development Of Cultured Meatmentioning
confidence: 99%
“…Although the initial cell adhesion efficiency and cell viability were low during cell culture using a serum-free medium, the cell growth efficiency was improved to a value close to that of the serum-containing medium through partial medium replacement and removal of antibiotics. In another study, Stout et al (2021) found that cell activity was maintained by subculturing bovine satellite cells in a serum-free medium and evaluated the possibility of reducing the medium cost by predicting the optimal amount of medium and additives. In particular, long-term cell expansion was possible when recombinant albumin was added to the developed Beefy-9 medium.…”
Section: Current Technologies In the Development Of Cultured Meatmentioning
confidence: 99%
“…Although substantial progress has been achieved in recent years by both for‐profit companies and academic groups, CM remains a relatively new area of investigation. As might be expected for a nascent field that draws heavily on knowledge gained from previous work aimed at a distinct set of problems, review, and perspective papers about CM (at least 50 by our estimate) [ 10–14,16,18,23,28,37,44,64–109 ] currently outnumber original research papers where CM production is the primary intended application (at least 24) [ 15,59,110–131 ] or CM‐related patents (at least 24). [ 132–155 ] These estimates do not include LCA or TEA studies, consumer acceptance studies, or purely computational analyses.…”
Section: Cultivated Meatmentioning
confidence: 93%
“…As a result, replacing FBS with serum-free supplements or chemically defined serum alternatives is desirable to eliminate animal-derived components from culture and to create media that have consistent performance. In recent years, the development of robust xeno-free medium formulations such as Essential 8™, TeSR™, and FBM™ has enabled the removal of serum from cell culture [85][86][87]. However, further advancements are still needed to create chemically defined media formulations that are consistently as effective as serum-based media in promoting cell growth, particularly for livestock animal cells [86,88,89].…”
Section: Culture Medium Considerationsmentioning
confidence: 99%